The Effect Of Community Participation, Transfotmational Leadership And Internal Control Systems On Accountability Financial Management Of Village Funds In Labu Beach District Village Deli Serdang - Henny Andriyani Wirananda; Wilda Sri Munawaroh Harahap (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to examine the effect of community participation, transformational leadership and internal control systems on the accountability of village fund financial management in Pantai Labu Village, Deli Serdang Regency. This research is a quantitative research. Data collection was carried out using a questionnaire. Questionnaires were distributed to each village apparatus, namely the village head, village secretary, finance department, BPD, and community leaders. The results of this study indicate that: (1) Community participation has no partial and significant effect on the Accountability of Village Fund Financial Management. (2) Transformational Leadership has a partial and significant effect on the Accountability of Village Fund Financial Management. (3) Transparency partially and significantly affects the Accountability of Village Fund Financial Management. (4) The Internal Control System partially and significantly influences the Accountability of Village Fund Financial Management. (5) Community Participation, Transformational Leadership, Transparency, and Internal Control Systems simultaneously and significantly influence the Accountability of Village Fund Financial Management.